Diurnal variation of human tear meniscus volume measured with tear strip meniscometry self-examination - Ayaki, Masahiko (PLoS One, 2019)
PURPOSE: Tear secretion is critical for maintenance of healthy ocular surface and vision. Most of normal subjects and dry eye patients feel worsening of ocular dryness in the afternoon, however, diurnal variation of tear meniscus volume has not been directly measured because there was no appropriate method. We used a simple, non-invasive technique, tear strip meniscometry (SM) by self-examination. Previous investigations indicated the values of SM correlated strongly with those of the Schirmer test, tests of tear break up time, and tear meniscus height measurement by anterior optical coherence tomography. The purpose of this study was to capture diurnal variation of aqueous availability at the tear meniscus by measuring wetted length using SM through self-examination. METHODS: Thirty-six medical personnel (mean age; 35.7 years) participated and SM self-examination was performed using a mirror seven times a day. The strip is applied for 5 seconds to the lateral side of the lower lid tear meniscus without touching the ocular surface. RESULTS: The measured SM value was the highest upon awakening (4.44 ± 3.14 mm) and gradually decreased in the evening; 3.81 ± 3.12 at 9:00, 3.31 ± 2.72* at 12:00, 2.89 ± 1.88* at 15:00, 2.92 ± 1.87* at 18:00, 2.78 ± 1.85* at 21:00, and 2.89 ± 1.75* at bedtime with statistical significance compared to the value upon awakening (*P < 0.05, Dunnett’s multiple comparison test). Proportion of number of subjects with low SM value (< 4 mm) to total number of subjects was 52.8% upon awakening and 83.3% at 21:00, and gradually increased toward evening. CONCLUSION: Our results could identify diurnal variation of tear meniscus volume in the general population.